1978
DOI: 10.1002/cpt1978233281
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and respiratory effects of morphine and butorphanol

Abstract: The hemodynamic effects of butorphanol, a potent synthetic narcotic-antagonist analgesic, were investigated and compared with those of morphine. A total of 20 patients were studied (8 butorphanol, 12 morphine) at the time of diagnostic cardiac catheterization. Butorphanol decreased pH, PCO2, and systemic artery pressure and increased PCO2, cardiac index, and pulmonary artery pressure. Morphine caused similar changes in pH, PO2, systemic artery pressure, and PCO2 but much smaller changes in cardiac index and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(24 citation statements)
references
References 6 publications
3
21
0
Order By: Relevance
“…Normally, the dominant control of ventilation is mediated through an increase in PaCO 2 , which strongly stimulates central chemoreceptors, 119 leading to increased ventilation. RD from morphine is characterized by a dose-related, naloxone-reversible depression of resting minute ventilation (Ve) with proportional reduction of tidal volume (Vt), [120][121][122] decreased PaO 2 and pH, increased PaCO 2 , 121,123 and decreased ventilatory drive stimulated by hypercapnia and hypoxia. 124,125 In volunteers, ITM caused a dose-related depression of medullary respiratory centre sensitivity to ventilatory stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Normally, the dominant control of ventilation is mediated through an increase in PaCO 2 , which strongly stimulates central chemoreceptors, 119 leading to increased ventilation. RD from morphine is characterized by a dose-related, naloxone-reversible depression of resting minute ventilation (Ve) with proportional reduction of tidal volume (Vt), [120][121][122] decreased PaO 2 and pH, increased PaCO 2 , 121,123 and decreased ventilatory drive stimulated by hypercapnia and hypoxia. 124,125 In volunteers, ITM caused a dose-related depression of medullary respiratory centre sensitivity to ventilatory stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Any possible significance has been determined considering it statistically significant if it's P < 5% level of significance. In 1978, Popio et al, 5 compared the haemodynamic and respiratory effects of Morphine and Butorphanol. A total of 20 patients were studied at the time of diagnostic cardiac catheterization.…”
Section: Methodsmentioning
confidence: 99%
“…Amide 12 was converted to the amine by reduction with LiAlH 4 , 16) and treated with HCHO and HCO 2 H to yield 13. After debenzylation using Pd(OH) 2 , acylation of the secondary amine gave the target compounds 5a and b. Compounds 6a and b were synthesized from 1-benzyl-4-piperidone (14) using the Horner-Wadsworth-Emmons reaction to give olefin 15.…”
Section: Synthesismentioning
confidence: 99%
“…11) Although intracerebroventricular pretreatment with an antiserum against dynorphin A (1-17) did not affect the antinociceptive effect induced by subcutaneous (s.c.) treatment of 1 and 2, the antinociceptive effect was greatly attenuated by intrathecal (i.t.) pretreatment with an antiserum against dynorphin A (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) in mice. This suggested that the antinociceptive effect induced by s.c. treatment of 1 and 2 occurred without binding to the KOR in the ventricles of the brain, in where might stimulate the descending dynorphinergic neuron and production of dynorphin in the spinal cord.…”
mentioning
confidence: 99%